1985
DOI: 10.1002/lipi.19850870502
|View full text |Cite
|
Sign up to set email alerts
|

Zum Nachweis von Sesamöl

Abstract: Es wird ein hochdruckfliissigkeitschromatographisches Bestimmungsverfahren zur gleichzeitigen Erfassung der Sesamolbestandteile Sesamol, Sesamolin und Sesamin neben den Tocochromanolen beschrieben. Eingesetzt werden Liisungen der Ole in n-Hexan oder das Unverseihare, in dem Sesamol jedochnicht bestimmbarist.DieTrennungerfolgt aneiner LiChre sorb Si 60.5 pm. 25 x 0.4 cm-Saule. Eluiert w i d mit 6% Dioxan in n-Hexan oder 10 % Ethylacetat in n-Hexan, detektiert wird die Fluoreszenzemission bei 330 nm nach Anregun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The differences in vitamin E contents among months were found to be significant (p a 0.01). Kanno et al [15] and Coors and Montag [16] reported that butter produced in summer contains more tocopherol than that produced in winter. The reason for the difference between summer and winter butters was type of feeding.…”
Section: Changes In Vitamin E Contentmentioning
confidence: 99%
“…The differences in vitamin E contents among months were found to be significant (p a 0.01). Kanno et al [15] and Coors and Montag [16] reported that butter produced in summer contains more tocopherol than that produced in winter. The reason for the difference between summer and winter butters was type of feeding.…”
Section: Changes In Vitamin E Contentmentioning
confidence: 99%